Football Metaphors in Bulgarian Political Discourse - Dosev, Vladimir (Media and Language, 2023)
According to the theory of cognitive linguistics, metaphors shape not just our communication, but also the way we think, act in our everyday life, and even vote. The aim of this article is to describe the manipulative usage of football metaphors in Bulgarian political discourse. The object of cognitive discourse analysis are political texts published in Bulgarian newspapers and on the Internet in the last 10 years. Bulgarian politicians and journalists often use metaphors and figurative language not only to amuse their audiences but also to influence the unconscious mind of the people.